PENERAPAN ASAS KEPATUTAN HUKUM TERHADAP PRAKTIK KONTRAK KOMERSIAL INTERNASIONAL BERBAHASA ASING DIHUBUNGKAN DENGAN UNDANG-UNDANG - Umah, Ummu Khoerul; Dwisvimiar, Inge; Arifinal, Mochamad (Gapenas Publisher, 2024)
Law Number 24 of 2009 concerning the Flag, Language, and National Emblem and the National Anthem Juncto Presidential Decree Number 63 of 2019 concerning has regulated that Indonesian is the language that must be used in contracts involving Indonesian private institutions, PT NKG and PT PCI in international commercial contracts in their companies only use English. This study aims to analyze the obligation to apply Indonesian in contracts and to determine the application of the principle of legal propriety in international commercial contracts that occur in PT NKG and PT PCI. This research method uses normative-empirical legal research, namely legal research that examines the provisions of laws and regulations (normative), namely Law Number 24 of 2009 Jo Presidential Decree Number 63 of 2019 in connection with commercial contracts at PT NKG and PT PCI. The results of the analysis show that Indonesian is the language that must be used in every contract, in addition, this study also finds that PT NKG and PT PCI do not fulfill the lawful cause so that they do not apply the principle of propriety. Therefore, the results of this study suggest that contracts made in Indonesia must use Indonesian so that the principle of propriety in contracts stated in Book III of the Civil Code remains implemented.